Measured and predicted sediment yield from a subtropical, heavy rainfall, steep-sided river basin: Hanalei, Kauai, Hawaiian Islands - Calhoun, R. S.; Fletcher, C. H. (Geomorphology, 1999)
To determine the sediment yield of the 54.4 km(2) Hanalei River basin, we employ three methods: (1) the Universal Soil Loss Equation (USLE), which uses natural characteristics of the basin such as the amount of rain, slope steepness and length values, and soil types to predict sediment erosion in a basin; (2) the thickness and calibrated radiocarbon age of fluvial deposits cored from the coastal plain; and (3) field measurements of suspended sediment in the river. Method 1 (USLE) provides a model prediction of sediment yield that we test with observational data of methods 2 and 3. Several curves, including one by the US Soil Conservation Service, predict a sediment delivery ratio (measured sediment yield: gross erosion) between approximately 15% and 50%. With 5260 +/- 2210 Mg (metric tons) yr(-1) of suspended sediment in the Hanalei River and 2300 +/- 700 Mg yr(-1) deposited on the coastal plain, however, the delivery of sediment in the Hanalei basin ranged between 45% and 101% of the maximum predicted USLE value (88 +/- 103 Mg km(-2) yr(-1)). This higher than predicted yield may be the result of mass movement. We are not able to differentiate, however, between erosion and mass movement as the principle agent of denudation. Our measurements indicate a total sediment yield of 140 +/- 55 Mg km(-2) yr(-1) for the Hanalei Valley. (C) 1999 Elsevier Science B.V. All rights reserved.
267flTimes Cited:14Cited References Count:37